Immunoexpression of S100A4 in canine skin melanomas and correlation with histopathological parameters - Grandi, Fabrizio [UNESP]; Rocha, Rafael M.; Miot, Hélio Amante [UNESP]; Cogliati, Bruno; Rocha, Noeme Sousa [UNESP] (Taylor & Francis Ltd, 2014)
Background: Melanoma is one of the most common skin neoplasms in humans and dogs. The tumor microenvironment in melanoma comprises cancer cells and stromal cells that interact to accelerate tumor progression. Several prognostic markers for melanomas have been studied in many human tumors, including fibroblast-specific protein 1 (S100A4). S100A4 is a member of the S100 family of calcium-binding proteins in stromal cells.Hypothesis/objectives: The objective of this study was to describe the immunohistochemical patterns of S100A4 in stroma and neoplastic cells of canine skin melanomas and correlate them with some histological parameters.Animals and Methods: Forty-eight samples (38 pigmented and 10 non-pigmented melanomas) were first selected and their nature confirmed using S100, Melan A and vimentin. All cases were examined by immunohistochemistry using S100A4 to correlate expression, histotype, and level of invasion.Results: All the tumors, including 10 non-pigmented, were positive for S100, Melan A, vimentin and negative for cytokeratin AE1/AE3 (consistent with melanomas). The 48 melanomas were classified as epithelioid (n = 21), spindle (n = 14), and mixed (n = 13). S100A4 was preferentially expressed in epithelioid and spindle cell types compared with mixed melanomas and S100A4 expression was not associated with level of invasion (Clark's levels IV to V).Conclusion: S100A4 expression in melanoma samples varied among histotypes but not between levels of invasion.
Keywords: dog; canine; melanoma; skin; fibroblast-specific protein 1; S100A4; stroma; immunohistochemistry